Impact of fiscal policies of the Philippines, Thailand, and Vietnam on MSMEs and their relative effects on GDP growth - John Luis Censon; Hoan Ferdinand Sanque; Richard Elliot Villegas; Ronaldo Cabauatan (Faculty of Science and Technology University of Pramita Indonesia, 2023)
Over the years, countries from Southeast Asia have MSME sectors that play a vital role in economic development of the region. Governments have their own strategies on how to deal with their economies, through fiscal policies, that serve the best interest of the condition of their states and citizens. As MSMEs in the Philippines, Thailand, and Vietnam continues to contribute employment of the vast majority of their populations, this study examines the effects of the fiscal spending of the aforementioned countries to their MSMEs and the relationship of the increase in number of MSMEs to aggregate national economic outputs. By using panel regression analysis, this paper aims to prove that fiscal policies, as measured using annual government expenditures data, together with household consumption, and MSME employment as supporting variables, would positively affect MSME growth, leading to a favorable outcome to GDP growth. This led to this paper providing insights that government expenditure and HFCE have positive significant relationship to the number of MSMEs in the Philippines, Thailand, and Vietnam, while MSME employment is negatively significant to it. With the rise of MSMEs in the selected countries, the PLS and RE results concluded that GDP growth of these countries can be influenced by their MSME growth. The outcome of this study could help policymakers and institutions to formulate sound government measures and recommendations to ensure that opportunities provided by the MSME in their economies are maximized.